SIMULASI PENGGUNAAN LOGIKA FUZZI PADA PENGENDALIAN I-AMPU LAI-U LINTAS - Djamarus, Djasli; Tjanggulung, Yuliana L (TEKNOINFO, 2007)
One of the major we faced in a big city is a traffic jam problem. Usually it is happened around traffic junctions controlled by a traffic light system. In a conventional traffic light, the traffic is controlled by giving a constant number of seconds for each direction at any time for the traffics to pass the junction.Even though the aim of the traffic light is to avoid or at least to reduce the traffic jam, in fact in a very dense traffic, the conventional traffic light is fail to comply with this situation. This paper addresses the design, implementation and analysis of an intelligent traffic light controller based on fuzzy logic technology to overcome the traffic problem.Graphical software is developed to simulate the situation of the traffic light junction based on this technology. The software allows simulation at a junction while cars from each junction can go straight or turn right controlled by fuzzy or conventional controller. The simulation results show that performance of fuzzy logic controller is better than traditional controller.